Prevalence and penetrance of ZFPM2 mutations and deletions causing congenital diaphragmatic hernia. (26th April 2014) - Longoni, M.; Russell, M.K.; High, F.A.; Darvishi, K.; Maalouf, F.I.; Kashani, A.; Tracy, A.A.; Coletti, C.M.; Loscertales, M.; Lage, K.; Ackerman, K.G.; Woods, S.A.; et al.
Abstract : Zinc finger protein, FOG2 family member 2 ( ZFPM2 ) (previously named FOG2 ) gene defects result in the highly morbid congenital diaphragmatic hernia (CDH) in humans and animal models. In a cohort of 275 CDH patient exomes, we estimated the prevalence of damaging ZFPM2 mutations to be almost 5%. Genetic analysis of a multigenerational family identified a heritable intragenic ZFPM2 deletion with an estimated penetrance of 37.5%, which has important implications for genetic counseling. Similarly, a low penetrance ZFPM2 frameshift mutation was observed in a second multiplex family. Isolated CDH was the predominant phenotype observed in our ZFPM2 mutation patients. Findings from the patients described herein indicate that ZFPM2 point mutations or deletions are a recurring cause of CDH.